Environmental maintenance and transmission of Francisella tularensis in cottontail rabbits, prairie voles, and amoebae - Brown, Vienna Rae, author; Bowen, Richard, advisor; Bachand, Annette, committee member; Pabilonia, Kristy, committee member; Petersen, Jeannine, committee member (Colorado State University. Libraries, 2016)
Tularemia is a zoonotic disease that is endemic in much of the Northern Hemisphere, capable of causing severe disease in a wide range of hosts. This disease is caused by the gram-negative bacterium Francisella tularensis and most human cases are caused by either subsp. tularensis (type A) or holarctica (type B). Genetic clustering has led to further differentiation within type A and type B strains; type A strains are currently classified as A1a, A1b, and A2. Due to the high virulence and low infectious dose of this pathogen, naïve immune status of the public, and previous weaponization, F. tularensis has been classified as a Tier 1 Select Agent by the Centers for Disease Control and Prevention. Although the Francisella bacterium was discovered over a century ago, understanding of ecological factors that contribute to environmental maintenance and transmission remains enigmatic. Extensive research has been performed in a variety of laboratory animal models to evaluate factors related to disease progression and vaccine and therapeutic options; however, very little is known about reservoir and/or amplification hosts in a natural setting. Reported here are a series of experimental studies performed in cottontail rabbits and voles as well as in vitro infections of amoebae with multiple strains of F. tularensis. The objectives of the in vivo studies were to characterize clinical disease, tissue dissemination and organ burden, and morbidity and mortality in a species believed to play an important role in naturally acquired infections. Rabbits were inoculated using a strain and dose of organism as well as a route of infection in accordance with what would be expected in nature. The initial experimental infections of cottontail rabbits involved intradermal inoculation with one of several strains of F. tularensis which resulted in varied patterns of clinical disease, gross pathology, and histopathology. Each of the type A strains was highly virulent, with rabbits requiring euthanasia or succumbing to infection 3-13 days post-infection. Gross lesions observed in infected rabbits included numerous microabscesses in the livers and spleens, suggesting high bacterial organ burdens. In contrast, most rabbits infected with type B strains developed a mild fever and became lethargic, but the disease was infrequently lethal. Those rabbits infected with type B strains that survived longer than 14 days post-infection developed a robust humoral immune response, and F. tularensis was not isolated from liver, spleen, or lungs of those animals. These findings depict a clear difference in virulence and immune kinetics between type A and B strains of F. tularensis in cottontail rabbits. Based on findings from the original study with cottontail rabbits, I evaluated the protection afforded against infection with a type A strain of F. tularensis by prior inoculation with a type B strain. Previous infection with a type B strain of the organism was found to lengthen survival time and, in some cases, prevented death following inoculation with a type A2 strain of F. tularensis. In contrast, inoculation of a type A1b strain was uniformly lethal in cottontail rabbits irrespective of a prior type B inoculation. These findings provide important insight about the role cottontail rabbits may play in environmental maintenance and transmission of this organism. Prairie voles are believed to acquire a natural infection with F. tularensis from contact with infected waterways or cannibalism of another vole that died from a tularemia infection. To evaluate such infection experimentally, I inoculated prairie voles orally with 107 organisms of type B F. tularensis and serially euthanized them to characterize organ burdens and pathology. The inoculated voles failed to show any clinical signs of disease and upon necropsy did not present with any gross lesions. Furthermore, organisms were not recovered from the liver and spleen, and antibodies were not detected, despite evaluation >14 days post-infection. Eight voles were then challenged intranasally with 350-650 organisms of one of two strains of F. tularensis. Infection with one strain (OR96-0246) resulted in all the animals succumbing to death or euthanasia between 6 and 7 days post-infection, whereas voles infected with the other strain (KY99-3387) survived to the end of the study period (10 days post-infection), with the exception of one vole which succumbed to infection. These findings were surprising and require further investigation to understand how voles become infected in nature and what role they may play in F. tularensis persistence and transmission. Free-living amoebae are capable of harboring pathogens and have been implicated in various disease outbreaks. I evaluated 3 strains of Acanthamoebae and 1 strain of Hartmannella as hosts for three bacterial pathogens. All strains of amoebae were propagated in culture with virulent strains of F. tularensis, Burkholderia pseudomallei and methicillin-resistant Staphylococcus aureus, with the aim of elucidating both general principles and pathogen-specific mechanisms associated with bacteria-amoebae interactions. F. tularensis and B. pseudomallei were recoverable from the lysate for all four strains of amoebae at both 4 and 24 hours post-inoculation, whereas MRSA was recoverable from the lysate of all four strains at the 4 hour time point and from only two of the strains at the 24 hour time point. Confocal microscopy allowed for the visualization of labeled bacteria of each strain and differentiation of amoebae morphology was possible. These findings provide intriguing evidence that amoebae are capable of phagocytosing pathogenic bacteria and that protozoa may play a role in environmental maintenance and persistence.